TYPE STUDIES IN THE CLAVARIOID FUNGI. V. THE TAXA DESCRIBED BY CASPAR VAN OVEREEM - RONALD H. PETERSEN (REINWARDTIA, 1980)
Type specimens of Javanese clavarias described by van Overeem — i.e. Clavaria depokensis. Clavaria luteo-tenerrima, Clavaria sanguineo-acuta and Clavulinopsis sulcata — are extant and well preserved in Herbarium Bogoriense. These are reexamined and reassigned to their respective genera and infrageneric complexes.